Secondary metabolites produced by endophytic fungi: Novel antifungal activity of fumiquinone B - Grigoletto, Diana Fortkamp; Correia, Ana Maria Lima [UNESP]; Abraham, Wolf-Rainer; Rodrigues, Andre [UNESP]; Assis, Marco Antonio [UNESP]; Ferreira, Antonio Gilberto; Massaroli, Michelli; De Lira, Simone Possedente (Universidade Estadual de Maringa, 2019)
Fungi are present in the most diverse environments including the interior of plant tissues, living as endophytes without causing apparent damage. These endophytes are producers of secondary metabolites, also known as natural products, such as fungicides. Here, we evaluated the ethyl acetate fractions obtained from endophytic fungi isolated from plants in the genus Begonia. The fractions were submitted to inhibitory test against the plant pathogens Diaporthe phaseolorum and Colletotrichum gloeosporioides. From the 88 ethyl acetate fractions evaluated, 14.7% inhibited C. gloeosporioides and 11.3% inhibited D. phaseolorum. One fungal isolate displaying an active fraction was selected for chemical investigation. The fungus identified as Neopestalotiopsis sp., produced a compound that was active against D. phaseolorum, with a MIC of 312 jig ml/1 (1,695.3 jiM). The compound was identified by mass spectrometry and 1H NMR as the known compound fumiquinone B. The results highlight that the endophytes are capable of producing compounds that may be used to control plant pathogens. The compound fumiquinone B is reported for the first time as an antifungal agent against D. phaseolorum, a relevant plant pathogen worldwide. This is also the first report of the production of fumiquinone B by the genus Neopestalotiopsis.
Keywords: 2,6-hydroxy-5-methoxy-3-methylcyclohexa-2; 5-diene-1,4-dione; Diaporthe phaseolorum; Neopestalotiopsis sp